(untitled) (Interdisciplinary Studies Journal, 2025)
Public policies protecting women in situations of violence were conceived as responses to historical demands for equal rights. In this context, several laws were enacted, most notably the Maria da Penha Law (number 11,340/2006), which emphasizes emergency protective measures. Given this scenario, the question arises: has the affirmation of rights been sufficient to ensure full protection for women victims of violence? The answer to this question can be seen as a public problem, since, in practice, many cities, including São Borja, in Rio Grande do Sul, lack essential structures such as shelters. The objective of this study is to demonstrate that the absence of these services cannot be interpreted as an indication of their irrelevance, but rather as evidence of the urgent need for their expansion, especially given the number of cases of violence against women. The research, qualitative and descriptive-analytical in nature, is based on a literature review, document analysis, and official data. It was concluded that the creation of a shelter in São Borja or the offering of alternatives to achieve this right would represent the fulfillment of the commitment assumed by the public entity, guaranteeing the effectiveness of the law and, consequently, offering alternatives for protection to victims.